Towards a Behavioral Model for Assets Pricing: Evidence from the Tunisian Stock Exchange - Houda, Ben Mabrouk; Abdelfettah, Bouri (Indian Journal of Finance, 2010)
The conception of a concise and rational model for assets pricing in an efficient market's context has been, for a long time, the axis of concern for the researchers of finance. This was warranted by the contributions of Sharpe (1964) Sharpe and Linter (1965) in their test to express the price of an asset by the systematic risk of this, last via the famous model of assets pricing known as the CAPM (Capital Assets Pricing Model). The identification of the systematic risk is initially on some theoretical bases, that it is about the CAPM developed by Sharpe (1964), Sharpe and Lintner (1965) and Mossin (1966) or of the theory of the arbitrage pricing theory (APT) introduced by Ross (1976) and illustrated by Chen, Roll and Ross (1986).